Realitas Pengelolaan Keuangan Desa: Dominasi dalam Pelaksanaan APB Desa di Kabupaten Mojokerto - Handono, Ardi Tri; Fanani, Zaenal (IAIN Kudus, 2018)
This research seeks to examine the experience and understanding of the financial managers of Waduk Gede Village in Mojokerto Regency. This is motivated by the implementation of the Village Law (UU No. 6 Tahun 2014) which has implications for increasing funds managed by the village, but in its management, various irregularities have been found. Case studies are used to understand the reality and the understanding of the informant. The findings indicate that the role of the Village Head is very dominant. Implementation of the APB Desa in Waduk Gede Village when compared to Permendagri No. 113 Tahun 2014 there are certainly some discrepancies. The implementation of Village APB Desa should be delegated to Implementation Team (TPK) or Village Financial Management Technical Officer (PTPKD)